Impact of Emotional Intelligence and Hedonistic Lifestyle on Financial Management with Self-Control as a Mediator - Nahda Wahyuningrum; Harsono Harsono (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study examines the influence of emotional intelligence and hedonistic lifestyle on financial management, with self-control as a mediating variable in these relationships.Method: This research employs a quantitative approach. Data were collected through online questionnaires distributed to students at the University of Muhammadiyah Surakarta who have experience managing personal finances. A purposive sampling technique was used, resulting in a sample of 151 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software.Result: The findings show that emotional intelligence positively and significantly affects financial management, while hedonistic lifestyle has no significant impact. Additionally, self-control mediates the relationship between emotional intelligence and financial management, but does not mediate the effect of hedonistic lifestyle.Practical Implications for Economic Growth and Development: The results emphasize the importance of psychological capacity building in financial education. By enhancing students' emotional intelligence and self-control, educational institutions can encourage more responsible financial behaviors that contribute to economic stability, reduce overconsumption, and foster sustainable growth among younger generations.Originality/Value: This research introduces a new model that demonstrates how self-control serves as a critical link between emotional intelligence and lifestyle factors affecting students' financial management. The study offers a fresh approach by examining the interaction of two opposing forces through a common mediating factor. The proposed model provides both theoretical insights and practical strategies for developing financial education programs grounded in psychological principles.